Peran Ekstra Menari dalam Mengembangkan Keterampilan Sosial Emosional Anak Kelompok A di RA Masjid Al Akbar Surabaya - Nailunnajah, Zulfah Agustin; Muallifah, Ilun (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2026)
Dancing as an outdoor activity significantly impacts the social and emotional skills of young children. They learn to express their emotions, work together in groups, and increase their self-confidence and empathy through dance activities. Several studies have shown that participating in dance activities can also help children manage their emotions, enhance social interactions, and improve their communication skills. Developmentally appropriate dance programs can positively impact their social and emotional development. Early children's ability to manage their own emotions is part of their emotional developmental maturation during the transition from the preoperational to the concrete operational stage. Early children's ability to manage their emotions is part of their emotional developmental maturation during the transition from the preoperational to the concrete operational stage. The ability to manage their own emotions can be seen in their ability to utilize their emotions positively, regulate their emotions according to their circumstances, and appropriately protect themselves from experiencing unhealthy emotions.